2013
DOI: 10.5005/jp-journals-10024-1281
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malocclusion among 12 to 15 Years Age Group Orphan Children using Dental Aesthetic Index

Abstract: Objective:The study was done to determine the prevalence of malocclusion and orthodontic treatment among orphan children. Materials and methods:The sample consisted of 165 orphan children aged between 12 and 15 years. A clinical examination was used to determine the orthodontic treatment need according to the Dental Aesthetic Index (DAI). The statistical software namely SPSS version 15.0 was used for the analysis different parameters as gender and age. Results:The prevalence of definite, severe and very severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
(8 reference statements)
1
5
0
Order By: Relevance
“…Similar findings were reported by Gauba et al (1998) and Suma et al (2011), while Ahammed et al (2013), Aikins et al (2011), Borzabadi-Farahani et al (2011), Shivakumar et al (2009 and Tak et al (2013) reported higher malocclusion scores among male subjects. However, Borzabadi-Farahani et al (2011), Babu andGopu (2011) andCavalcanti et al (2013) found no correlation of treatment need with gender.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar findings were reported by Gauba et al (1998) and Suma et al (2011), while Ahammed et al (2013), Aikins et al (2011), Borzabadi-Farahani et al (2011), Shivakumar et al (2009 and Tak et al (2013) reported higher malocclusion scores among male subjects. However, Borzabadi-Farahani et al (2011), Babu andGopu (2011) andCavalcanti et al (2013) found no correlation of treatment need with gender.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, this study was carried out to assess prevalence of malocclusion and orthodontic treatment need among high school students in Mangalore city, India. The study population was larger than studied by Ahammed et al (2013) and Babu and Gopu (2011); however, Aikins et al (2011), Ajayi (2008, Cavalcanti et al (2013), Dacosta (1999), Gábris et al (2006) and Tak et al (2013) evaluated larger population groups. Since the schools surveyed were selected by random sampling, the results of this study have good external validity.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…OHRQoL is associated with self-related oral health; subjective symptoms of temporomandibular disorders (TMDs); oral pain and stomatitis; decayed, missing, and filled teeth (DMFT); and malocclusions [ 2 ]. Malocclusions are one of the major oral health problems ranking third after dental caries and periodontal disease [ 3 ]. It affects periodontal health and increases the risk of dental caries, traumatic dental injuries and temporomandibular joint problems [ 4 ].…”
Section: Introductionmentioning
confidence: 99%